(untitled) (American Journal of Islam and Society, 2005)
Question 1: Who are the moderate Muslims, and what are their beliefs and politics? FAR: The debate among the participants shows that while the term moderate Muslim is problematic, there is a need to define the attitudinal difference between Muslims who can be worked with from those who cannot. I suggest that the defining feature is between those who believe in a pluralist, multicultural, multi-religious societal contract that allows for differences of opinions within an over-arching construct, as opposed to those who believe in a societal contract that has no space for other religions, ethnicities, or cultures, or even intra-Islamic differences of opinion.1 The latter attitude leads to the phenomenon known as “Islamist terrorism,” the modern-day version of the seventh-century Kharijites, who fought and ultimately assassinated Ali, Prophet Muhammad’s son-in-law, and who, over the following century, developed a political philosophy that justified murdering fellow Muslims, including innocent women and children. Contemporary Muslims need to support that aspect of the war on terror that is a true jihad against all forms of terrorism, known in classical Islamic jurisprudence as hirabah, and anarchic terrorism that tears the social fabric essential to well-functioning societies. But this cannot be done without simultaneously purging Muslim societies of some other modern “isms” that have “terrorized” Muslims and still continue to deny them their inalienable human rights under the Shari`ah.2 One is fascism in the Muslim world, whether wrapped in a secular veneer like that of Saddam Hussein in Iraq or in an Islamic veneer like that of the Taliban in Afghanistan. Another is nationalism, a modernized form of pre-Islamic tribalism that Muslim theologians call `asabiyah and that more properly belongs to the jahili (pre-Islamic) time. This idea can morph into the modern form of Islamic nationalism that, in turn, leads to religious authoritarianism, which oppresses those Muslims and non-Muslims who follow authentic and legitimate religious interpretations that dare to differ from the “official” versions, and brands anyone who does not accept its point of view as an infidel, thereby arrogating to itself a right that the Prophet declared belongs only to God ...